Time-of-flight depth image denoising using prior noise information - Edeler, T; Ohliger, K; Hussmann, S; Mertins, A (IEEE 10th INTERNATIONAL CONFERENCE ON SIGNAL PROCESSING PROCEEDINGS, 2010)
In this paper, we propose a novel way of using time-of-flight camera depth and amplitude images to reduce the noise in depth images with prior knowledge of spatial noise distribution, which is correlated with the incident light falling on each pixel. The denoising is done in wavelet space and the influence and implications of the extended noise model to wavelet space and common denoising methods are shown.